Integration of Solvent Extraction and Non-Catalytic Esterification for the Treatment of Acidic Feedstocks - Busto, Mariana (2020)
The possibility of directly feeding the extract of a liquid-liquid extraction unit to a chemical reactor is analyzed. An example of extraction and noncatalytic esterification of naphthenic acids from acid petroleum crudes is used. Methanol is used both as a solvent and as a reactant. Separate tests of extraction and reaction are performed, and the performance of an integrated process is deduced by computer simulation. Thermodynamic and kinetic parameters for the extraction of naphthenic acids from an acid crude were determined. A partition coefficient of m = 0.66 at 60 °C between the alcoholic and petroleum phases was found. Three successive batch extractions with a 1:1 v/v ratio reduced the acidity from 4.3 to about 1.1 mgKOH g-1. Naphthenic acid concentrates were reacted with supercritical methanol in a batch reactor at high temperatures (280 °C), yielding naphthenic esters. Reaction of 1-2 h with methanol-to-oil molar ratios of 3-6 yielded 92-96% conversion because of a relatively low value of the equilibrium constant. Total conversion could, however, be achieved with the highly diluted extracts. Simulations were run using three countercurrent mixer-settlers and a noncatalytic reactor. The results indicated that extraction/supercritical esterification is a convenient pretreatment step of acidic feedstocks because of its simplicity, the good quality of the deacidified feedstock (acidity <0.5 mgKOH g-1), the total removal of the acids, and the good properties of the ester product as a fuel additive. Characterization of the methyl naphthenate product showed that it had a lower viscosity than the crude or the naphthenic acids; a high flash point; and total miscibility in gasoline, kerosene, and diesel. These and other properties showed that it could be sent to the diesel or fuel oil pools.